(3QSGdI aj GdYed HGdQHY GdeLjHs - (3bQg MUGQj, CMeO fjGRj Hf MSfs
(3ChdgG (B:s
(3GdMeO ddg gPg QSGdI eNJUQI aj GdYed HGdQHY GdeLjH eTJedI Ydi ebOeI hKeGfjI (B, (3GdebOeI aj GdQShe GdeQcR gh GdMRe GdPj ajg GdNjW hjSei GdbWH hbhS GdGQJaGY gj GdeMjWI HGdQShes
(3BNQgG (B:s
(3hEf TFJ RO HYO GdbWQ Ydi LjH GdGQJaGY aj GdLfhH hgPG GdaVd HjfgeG aj GdTeGd aeG cGf agh CUd GdeYOhd VY CUd GdeWdb Ydjg ef GdLjhH GdeHShWI aeG bWYg GdNjW Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs